Sistem Informasi Geografis Penyedia Jasa Rumah Kos Berbasis Website (Studi Kasus: Wilayah Kotabumi Lampung Utara) - Ferly Ardhy (Institut Informatika dan Bisnis Darmajaya, 2018)
Geographic Information System is a special information system that manages data that has spatial information (spatial reference). Or in a narrower sense, is a computer system that has the ability to build, store, manage and display geo-referenced information, such as data identified by its location in a database. With this rapid technological progress, the author tries to implement one of the GIS application program into the form of Kost Home layout information in Kotabumi. The author tries to build an application that will help to simplify the search such as information about home boarding services, home boarding locations, and strategic location of boarding house. The system to be created is